2010
DOI: 10.1007/s11011-010-9204-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that 2-methylacetoacetate induces oxidative stress in rat brain

Abstract: In the present study we investigated the effects of 2-methylacetoacetate (MAA) and 2-methyl-3-hydroxybutyrate (MHB), the major metabolites accumulating in mitochondrial 2-methylacetoacetyl-CoA thiolase (KT) and 2-methyl-3-hydroxybutyryl-CoA dehydrogenase (MHBD) deficiencies, on important parameters of oxidative stress in cerebral cortex from young rats. We verified that MAA induced lipid peroxidation (increase of thiobarbituric acid-reactive substances (TBA-RS) and chemiluminescence values), whereas MHB did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Several patients with T2 deficiency developed chronic neurological impairment, mainly extrapyramidal, independent of frank ketoacidosis (Buhaş et al, ; Fukao et al, ; Paquay et al, ). In vitro studies indicate that 2MAA and 2M3HB exert neurotoxic effects (Leipnitz et al, ; Rosa et al, ). Therefore, accumulated isoleucine‐catabolic metabolites may contribute to neurological impairment in patients with T2 deficiency (Fukao et al, ; Paquay et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several patients with T2 deficiency developed chronic neurological impairment, mainly extrapyramidal, independent of frank ketoacidosis (Buhaş et al, ; Fukao et al, ; Paquay et al, ). In vitro studies indicate that 2MAA and 2M3HB exert neurotoxic effects (Leipnitz et al, ; Rosa et al, ). Therefore, accumulated isoleucine‐catabolic metabolites may contribute to neurological impairment in patients with T2 deficiency (Fukao et al, ; Paquay et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, an increasing body of evidence indicates that chronic neurological impairment, mainly extrapyramidal manifestations, can exist independent of frank ketoacidosis even in patients with T2 deficiency confirmed at the molecular level (Buhaş et al, 2013;Fukao et al, 2018;Paquay et al, 2017). In vitro studies indicate that 2MAA and 2M3HB exert neurotoxic effects (Leipnitz et al, 2010;Rosa et al, 2005).…”
Section: Biochemical and Laboratory Significancementioning
confidence: 99%
“…Evidence supports a direct neurotoxic mechanism in T2D. A metabolite that is specific to T2D, 2‐methylacetoacetate, can induce oxidative stress in rat cerebral cortex . Also, hereditary deficiency of the preceding enzyme of isoleucine degradation, 2‐methyl‐3‐hydroxybutyryl‐CoA dehydrogenase, has been associated with choreoathetoid movements and abnormal basal ganglia imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Does accumulation of 2M3HB and 2AcAc result in basal ganglia lesions, leading to extrapyramidal manifestation? There are only a few reports about a direct influence of these compounds on brain function [79,80]. They showed that these compounds inhibited aerobic energy metabolism in the TCA cycle and the mitochondrial respiratory chain and induced oxidative stress in rat brain cortex in vitro.…”
Section: Neurological Manifestationmentioning
confidence: 99%